Respected Members,
I have a few doubts in Calculus. I hope if you can spare some amount of your valuable time and solve them and **explain their solutions**. They are as follows:

1) \(\frac { { d }^{ 20 }y }{ d{ x }^{ 20 } } (2\cos { x } \cos { 3x) } \) is equal to

a) \({ 2 }^{ 20 }(\cos { 2x } -{ 2 }^{ 20 }\cos { 3x } )\)

b) \({ 2 }^{ 20 }(\cos { 2x } +{ 2 }^{ 20 }\cos { 4x } )\)

c) \({ 2 }^{ 20 }(\sin { 2x } +{ 2 }^{ 20 }\sin { 4x } )\)

d) \({ 2 }^{ 20 }(\sin { 2x } -{ 2 }^{ 20 }\sin { 4x } )\)

Answer: (b)

2) \(\frac { { d }^{ n } }{ d{ x }^{ n } } (\log { x) } \) =

a) \(\frac { (n-1)! }{ { x }^{ n } } \)

b) \(\frac { n! }{ { x }^{ n } } \)

c) \(\frac { (n-2)! }{ { x }^{ n } } \)

d) \({ (-1) }^{ n-1 }\frac { (n-1)! }{ { x }^{ n } } \)

Answer:(d)

3) If **f(0) = 0, f'(0) = 2**, then the derivative of y = f(f(f(f(x)))) at x=0 is

a) 2

b)8

c)16

d)4

Ans: (c)

4) Suppose f(x) = \({ e }^{ ax }+{ e }^{ bx }\), where \(a\neq b\), and that **f"(x)-2f'(x)-15f(x)=0 for all x. Then the product ab is

(a) 25

(b)9

(c)-15

(d)-9

Answer (c)

5) If f(x) satisfies the relation

\(f(\frac { 5x-3y }{ 2 } )\quad =\quad \frac { 5f(x)-3f(y) }{ 2 } \) for all x,y\(\in \) R,

and f(0) = 3 and f'(0) = 2, then the period of sin(f(x)) is

a) 2\(\pi\)

b)\(\pi\)

c)3\(\pi\)

d)4\(\pi\)

Answer: (b)

Thanks and regards

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewest2) \(\dfrac{d(\log_{}{x})}{dx}=\dfrac{1}{x}\)

\(\dfrac{d^2(\log{}{x})}{dx^2} = -\dfrac{1}{x^2}\)

\(\dfrac{d^3(\log{}{x})}{dx^3} = \dfrac{2}{x^3}\)

\(\dfrac{d^4(\log{}{x})}{dx^4} = -\dfrac{6}{x^4}\)

\(\dfrac{d^5(\log{}{x})}{dx^5} = \dfrac{24}{x^5}\)

\(\dots\)

\(\dfrac{d^n(\log{}{x})}{dx^n} = (-1)^{n-1}\dfrac{(n-1)!}{x^n}\)

Log in to reply

Observe the pattern on repeated differentiation.

The derivative of y=f'(f(f(f(x)))). f'(f(f(x))). f'(f(x)). f'(x) . Now substitute the given values.

Simply differentiate and put the appropriate values in the given equation. You will get the values of a and b from there.

The function which satisfies the function equation \(f\left( \dfrac{a+b}{2} \right)=\dfrac{f(a)+f(b)}{2}\) can be taken as \(f(x)=A.x\) and from the given values you can find the value of A. IN this case the value of A will come out to be 2. Hence the fundamental period of sin(f(x)) will be \(\pi\).

I've given the hints and the approaches of all your doubts. Now you can try and surely it will help you.

All the best! @Manish Dash

Log in to reply

In question 5, you said \(f(x) = A \cdot x \)

In these types of question,i am always been confused in identifying \(f(x)\).

How do you come to know that f(x) will be \(A \cdot x \).

Log in to reply

Thank you very much @Sandeep Bhardwaj Sir!

Log in to reply

@Sandeep Bhardwaj , @Calvin Lin , @Brian Charlesworth

Log in to reply

1) \(2\cos x\cos 3x = \cos 2x+\cos 4x\)

\(\dfrac{d}{dx}(\cos 2x+\cos 4x) = -2^{1}(\sin 2x + 2^{1}\sin 4x)\)

\(\dfrac{d^{2}}{dx^{2}}(\cos 2x+\cos 4x) = -2^{2}(\cos 2x + 2^{2}\cos 4x)\)

\(\dfrac{d^{3}}{dx^{3}}(\cos 2x+\cos 4x) = 2^{3}(\sin 2x + 2^{3}\sin 4x)\)

\(\dfrac{d^{4}}{dx^{4}}(\cos 2x+\cos 4x) = 2^{4}(\cos 2x + 2^{4}\cos 4x)\)

\(\dfrac{d^{5}}{dx^{5}}(\cos 2x+\cos 4x) = -2^{5}(\sin 2x + 2^{5}\sin 4x)\)

\(\dots\)

\(\dfrac{d^{20}}{dx^{20}}(\cos 2x+\cos 4x) = 2^{20}(\cos 2x + 2^{20}\cos 4x)\)

Log in to reply

I don't understand derivatives enough to do the other three, but this may help:

3) \(f'(0)=0\)

\(f'(f(0))=0\)

\(f'(f(f(0)))=f(0)\)

Both sides of all the above equations are equal.

4) \(\frac{d}{dx}(e^{ax}+e^{bx})=ae^{ax}+be^{bx}\)

Log in to reply

nope. The very last expression is wrong, because \(ae^{ax} \neq e^{x} (ae^{a}) \), and such is the same for \(b\).

Log in to reply

Oh right. Sorry. Thanks!

Log in to reply

f (x)=\sqrt {1+cos^{2}\times(x^{2})}

Log in to reply

How to find f dash x

Log in to reply